„Mała Wiera” (1988) – „czegoś tak obrzydliwego w naszym kraju jeszcze nie było…”. Оburzeni przeciw oświeconym. Przyczynek do studium nad mentalnością „homo sovieticus” u progu nowej ery - Kistowska, Maria Natalia (Studia Rossica Posnaniensia, 2012)
The article is thought to be a contribution to a study on the mentality of homo sovieticus on the edge of a crucial period – perestroika. The basic material for the author were letters written by the audience to a movie screenwriter, Maryia Khmielik, and published as the last chapter of a film-based novel, both with the same title – Little Vera. This large body of voices stands up against – in their opinion – shameless and vile erotic scenes and against those few home truths which are presented. The portrait of homo sovieticus is fished out from fragments of the letters. Homo sovieticus seems to be sad, miserable, helpless and adrift in a new reality – just like the film’s characters.